Successful endovascular recanalization of massive cerebral venous sinus thrombosis in a patient with tuberous sclerosis and protein S deficiency: a case report. Issue 7 (12th July 2019) - Nishiyama, Yasuhiro; Ueda, Masayuki; Muraga, Kanako; Ota, Takahiro; Horikawa, Hiroshi; Kimura, Kazumi
Abstract: Here, we report the case of a 27-year-old woman with tuberous sclerosis complex who underwent successful endovascular intervention for cerebral venous thrombosis at the superior sagittal sinus. She had protein S deficiency and a long-term history of anemia caused by menorrhagia from uterine fibroids, possibly leading to a hypercoagulable state. Cerebral venous sinus thrombosis accounts for 0.5–1% of all strokes. Several cases of venous thrombosis in patients with tuberous sclerosis complex and protein S or protein C deficiency have been reported, but further studies are needed to identify whether an association of this rare combination may be explained.